Preferential FGF18/FGFR activity in pseudoglandular versus canalicular stage human lung fibroblasts - Belgacemi, Randa; Cherry, Caroline; El Alam, Imad; Frauenpreis, Andrew; Glass, Ian; Bellusci, Saverio; Danopoulos, Soula; Al Alam, Denise (Frontiers in Cell and Developmental Biology, 2023)
Fibroblast growth factor (FGF) signaling is necessary for proper lung branching morphogenesis, alveolarization, and vascular development. Dysregulation of FGF activity has been implicated in various lung diseases. Recently, we showed that FGF18 promotes human lung branching morphogenesis by regulating mesenchymal progenitor cells. However, the underlying mechanisms remain unclear. Thus, we aimed to determine the role of FGF18 and its receptors (FGFR) in regulating mesenchymal cell proliferation, migration, and differentiation from pseudoglandular to canalicular stage. We performed siRNA assays to identify the specific FGFR(s) associated with FGF18-induced biological processes. We found that FGF18 increased proliferation and migration in human fetal lung fibroblasts (HFLF) from both stages. FGFR2/FGFR4 played a significant role in pseudoglandular stage. HFLF proliferation, while FGFR3/FGFR4 were involved in canalicular stage. FGF18 enhanced HFLF migration through FGFR2 and FGFR4 in pseudoglandular and canalicular stage, respectively. Finally, we provide evidence that FGF18 treatment leads to reduced expression of myofibroblast markers (ACTA2 and COL1A1) and increased expression of lipofibroblast markers (ADRP and PPARγ) in both stages HFLF. However, the specific FGF18/FGFR complex involved in this process varies depending on the stage. Our findings suggest that in context of human lung development, FGF18 tends to associate with distinct FGFRs to initiate specific biological processes on mesenchymal cells.